Epidemiological and occupational profile of eye trauma at a referral center in Espírito Santo, Brazil - Milanez,Miquele (2017)
ABSTRACT Objective: To draw an epidemiological and occupational profile of eye trauma at a Brazilian referral center, make comparisons with the literature and provide subsidies for the adoption of adequate prevention and enforcement measures. Methods: Descriptive and prospective epidemiological study using a standardized questionnaire to collect data from 60 patients presenting with eye trauma at an ophthalmology service (HUCAM) between 1 april 2013 and 1 october 2013. Results: The male gender was predominant (80%). Ages ranged from 8 to 60 years. Most accidents (56.7%) occurred in the workplace, followed by the home (28.3%). Most injuries were closed, predominantly contusions, followed by foreign body on the external eye. Importantly, 82.9% of the victims of work-related trauma wore no eye protection at the time of the accident. Conclusions: Eye trauma in the workplace and elsewhere is an important problem of public health as it affects primarily the economically active population and may have serious consequences. A considerable proportion of eye trauma is easily avoidable by using personal protective equipment. To minimize the incidence of eye trauma, more attention should be given to instruction in and enforcement of the use of such equipment, supported by frequent prevention campaigns.